2021
DOI: 10.1186/s12301-021-00121-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after neonatal pyeloplasty in antenatally diagnosed uretero-pelvic junction obstruction

Abstract: Background With routine antenatal ultrasonography, fetal hydronephrosis is commonly diagnosed. This leads to early detection of postnatal uretero-pelvic junction obstruction which may require surgical intervention. But, there is no clear consensus in the benefits of operating these patients in the neonatal age. Methods Aim—To study the functional outcome after pyeloplasty in neonates with antenatally diagnosed unilateral uretero-pelvic junction obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…There was a study on neonatal pyeloplasty outcomes by Bendre et al . [ 11 ] that showed improvement in SRF from 35.48% to 44.7% in neonates with a mean age of 26 days. In our study, the youngest infant was 28 days old, which showed a drastic improvement in SRF from 29% to 50%.…”
Section: Discussionmentioning
confidence: 99%
“…There was a study on neonatal pyeloplasty outcomes by Bendre et al . [ 11 ] that showed improvement in SRF from 35.48% to 44.7% in neonates with a mean age of 26 days. In our study, the youngest infant was 28 days old, which showed a drastic improvement in SRF from 29% to 50%.…”
Section: Discussionmentioning
confidence: 99%